If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-7 + -8n) = 2(11 + 12n) + 2n (-7 * -4 + -8n * -4) = 2(11 + 12n) + 2n (28 + 32n) = 2(11 + 12n) + 2n 28 + 32n = (11 * 2 + 12n * 2) + 2n 28 + 32n = (22 + 24n) + 2n Combine like terms: 24n + 2n = 26n 28 + 32n = 22 + 26n Solving 28 + 32n = 22 + 26n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-26n' to each side of the equation. 28 + 32n + -26n = 22 + 26n + -26n Combine like terms: 32n + -26n = 6n 28 + 6n = 22 + 26n + -26n Combine like terms: 26n + -26n = 0 28 + 6n = 22 + 0 28 + 6n = 22 Add '-28' to each side of the equation. 28 + -28 + 6n = 22 + -28 Combine like terms: 28 + -28 = 0 0 + 6n = 22 + -28 6n = 22 + -28 Combine like terms: 22 + -28 = -6 6n = -6 Divide each side by '6'. n = -1 Simplifying n = -1
| 7-28c^2=0 | | 10x+8=11x+-4 | | 7(8+x)=91 | | -0.456=-0.3(7n-31.2) | | 3(x+5)+4= | | 4(5x+10)=140 | | x+23=-64 | | 4=4m+5-5 | | x^6+4027=0 | | x-9=42 | | 3c+8n= | | x+4=5x-8 | | 8-15t^2+14t=0 | | 8(y-2)=7(y-9) | | 3x+12=12-4x | | 2n+5c= | | 14x-10=11x+5 | | -10+-12m+16=90 | | 3z+5=4z | | (9+n)x=21x | | -8(x-8)+9(2x+2)=9(x+8)-6 | | 8+8(4p-8)=8(3p-1) | | -5X+3Y+18=0 | | 25=15x-1.86x^2 | | 3x-8y=13 | | u^2-14u+45= | | x^4-41x^2=400 | | 8y-2=342 | | -12r+4=-15 | | 12+x=19 | | (3x+6)=(4x-17) | | -12r+4r=-15 |